IMPROVING LISTENING ABILITY USING SONG - Adjie Hadrian; Rika Luci Aryani (IKIP Siliwangi, 2019)
Listening is skill that seem very difficult to be mastered, because it needs more attention and concentration to comprehend the sounds (listening material).Teachers always uses their students, they may become interesting for one of the teaching which can make the students milirtes in studying is listening to song’s. They will not understand what they study wel as a result, the use of song is impelemented in this research to improve students’ listening skill. The researcher uses classroom action research method with 2 cycles at seven grade Students of MTs Nurul Wahab. Pre test is given to students before treatment while post test given in each cycle. The data analysis is conducted by calculating the mean score of each post test and compare it with minimum standard score (KKM).As the result, the pre test mean score is 59.3. The post test cycle 1 is 69.4 and the post test 2 is 77.5. The data shows students’ improvement in each cycle, There are 42% of students who pass KKM in pre test, 66% students pass KKM in post test 1 and 87.5% of students pass KKM in post test 2. By calculating the percentage of each test, 75% of students pass KKM. Key Words: Song, Listening , Classroom Action Researchl